Kajian Dampak Pertumbuhan Sepeda Motor Terhadap Dcelakaan Lalu Lintas Dan Konsumsi Bbm - Nurdjanah, Nunuj (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Growth in number of motorcycles that have an impact so rapidl.y than indicated on the number ofaaidents, al.so have an impact on fuel amsumption. Acamhng to motorcycle users can save the useof fuel and transportation costs, but on a natianal. scale the high number of motorCtjCle sparked thehigh fuel consumption, -particularly in subsidized fuel.This studtj aims to determine how much impact the growth of motorCt;cle fuel consumption andtraffic accidents nationwide. The analysis used in this studt; uses descriptive methods and Simplelinear Regression.Based on the analysis significantly proven that the growth of motorcycle acci.dent has resulted inincreased traffic and fuel consumption nationally with a fairly strong correlation.Keywords: Growth Motorcycles, Tmffic Accidents, Fuel Consumption